Value of contrast-enhanced MRA versus time-of-flight MRA in acute ischemic stroke MRI - Boujan, Timan; Neuberger, Ulf; Pfaff, Johannes; Nagel, Simon; Herweh, Christian; Bendszus, Martin; Möhlenbruch, Markus Alfred (American journal of neuroradiology, 2018)
Background and purpose: Vessel imaging in acute ischemic stroke is essential to select patients with large-vessel occlusion for mechanical thrombectomy. Our aim was to compare the diagnostic accuracy of time-of-flight MR angiography and contrast-enhanced MR angiography for identification of vessel occlusion and collateral status in acute ischemic stroke. - Materials and methods: One hundred twenty-three patients with stroke with large-vessel occlusion before thrombectomy were included in this retrospective study. Before thrombectomy, 3T MR imaging, including conventional 3D TOF-MRA of the intracranial arteries and contrast-enhanced MRA of intra- and extracranial arteries, was performed. Both techniques were assessed independently by 2 neuroradiologists for location of the occlusion, imaging quality, and collateral status. Findings were compared, with subsequent DSA as the reference standard. - Results: Both techniques had good interrater agreement of κ = 0.74 (95% CI, 0.66–0.83) for TOF-MRA and κ = 0.72 (95% CI, 0.63–0.80) for contrast-enhanced MRA. Occlusion localization differed significantly on TOF-MRA compared with DSA (P < .001), while no significant difference was observed between DSA and contrast-enhanced MRA (P = .75). Assessment of collaterals showed very good agreement between contrast-enhanced MRA and DSA (94.9% with P = .25), but only fair agreement between TOF-MRA and DSA (23.2% with P < .001). - Conclusions: Contrast-enhanced MRA offers better diagnostic accuracy than TOF-MRA in acute ischemic stroke. Contrast-enhanced MRA was superior in localizing vessel occlusion within a shorter acquisition time while providing a larger coverage, including extracranial vessels, and a more accurate assessment of collateral status. These results support inclusion of contrast-enhanced MRA in acute stroke MR imaging, perhaps making TOF-MRA superfluous.
Gesehen am 07.05.2019